Пассивация поверхности высокочистых гранулированных металлов: цинка, кадмия, свинца - Пироженко, Л.А.; Пояркова, С.С.; Щербань, А.П.; Горбенко, Ю.В.; Рыбка, А.В. (Технология и конструирование в электронной аппаратуре, 2017)
Разработаны новые составы и режимы для химического травления и пассивации поверхности высокочистых гранул Zn, Cd и Pb с использованием неводных растворов электролитов. Это позволило получить гранулы металлов с тонкими сплошными устойчивыми оксидными пленками, которые можно хранить в обычных условиях на протяжении длительного времени без изменения состояния поверхности. Показана возможность применения смеси глицерина с ДМФА в качестве охлаждающей жидкости в процессе получения гранул свинца. Розроблено нові режими хімічного травлення і пасивації поверхні високочистих гранульованих Zn, Cd і Pb з використанням неводних розчинів електролітів. Це дозволило отримати гранули металів з тонкими суцільними стійкими оксидними плівками, які можна зберігати в звичайних умовах протягом тривалого часу без зміни стану поверхні. Показано можливість застосування суміші гліцерину з ДМФА як охолоджуючої рідини в процесі отримання гранул свинцю. For the high purity metals (99.9999%), such as zinc, cadmium, and lead, which are widely used as initial components in growing semiconductor and scintillation crystals (CdTe, CdZnTe, ZnSe, (Cd, Zn, Pb) WO4, (Cd, Zn, Pb) MoO4 et al.), it is very important to ensure reliable protection of the surface from oxidation and adsorption of impurities from the atmosphere. The specific features of surface passivation of high purity cadmium, lead and zinc are not sufficiently studied and require specific methodologies for further studies. The use of organic solutions in the schemes of chemical passivation of the investigated metals avoids hydrolysis of the obtained protective films. The use of organic solvents with pure cation and anion composition as the washing liquid prevents chemisorption of ions present in the conventionally used distilled water. This keeps the original purity of the granular metals. Novel compositions of etchants and etching scheme providing simultaneous polishing and passivation of high purity granular Zn, Cd and Pb are developed. Chemical passivation allows storing metals in the normal atmospheric conditions for more than half a year for Zn and Cd and up to 30 days for Pb without changing the state of the surface. The use of the glycerol-DMF solution in the processes for obtaining Pb granules provides self-passivation of metal surfaces and eliminates the additional chemical processing while maintaining the quality of corrosion protection.